Differential expression and localization of expansins in Arabidopsis shoots: implications for cell wall dynamics and drought tolerance - Balkova, Darina; Mala, Katerina; Hejatko, Jan; Panzarova, Klara; Abdelhakim, Lamis; Pleskacova, Barbora; Samalova, Marketa (Frontiers in Plant Science, 2025)
Expansins are cell wall-modifying proteins implicated in plant growth and stress responses. In this study, we explored the differential localization of expansins in Arabidopsis thaliana shoots, with a focus on EXPA1, EXPA10, EXPA14, and EXPA15 utilizing pEXPA::EXPA translational fusion lines. Employing the chemically inducible system pOp6/LhGR for EXPA1 overexpression and high-throughput automatic phenotyping we evaluated the drought response and photosynthetic efficiency under stress conditions. We observed distinct expression patterns of expansins, with EXPA1 primarily localized in stomatal guard cells, while EXPA10 and EXPA15 showed strong cell wall (CW) localization in epidermal and other tissues. Overexpression of EXPA1 resulted in pronounced changes in CW-related gene expression, particularly during early stages of induction, including the upregulation of other expansins and CW-modifying enzymes. The induced EXPA1 line also displayed significant morphological changes in shoots, including smaller plant size, delayed senescence, and structural alterations in vascular tissues. Additionally, EXPA1 overexpression conferred drought tolerance, as evidenced by enhanced photosynthetic efficiency (Fv/FM), and low steady-state non-photochemical quenching (NPQ) values under drought stress. These findings highlight the critical role of EXPA1 in regulating plant growth, development, and stress response, with potential applications in improving drought tolerance in crops.